2021
DOI: 10.3390/s21134425
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in ZnO-Based Carbon Monoxide Sensors: Role of Doping

Abstract: Monitoring and detecting carbon monoxide (CO) are critical because this gas is toxic and harmful to the ecosystem. In this respect, designing high-performance gas sensors for CO detection is necessary. Zinc oxide-based materials are promising for use as CO sensors, owing to their good sensing response, electrical performance, cost-effectiveness, long-term stability, low power consumption, ease of manufacturing, chemical stability, and non-toxicity. Nevertheless, further progress in gas sensing requires improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…The improvement in the transmission properties of the ARHCFs should also allow them to be successfully used in the broadband spectroscopy applications, i.e., in the frequency comb spectroscopy [62], which will enable an in-depth analysis of the complex mixture of gaseous substances, maintaining a low-volume of the sensing unit with high detection capability. Currently, the ARHCF-based gas sensors are in majority realized in laboratory conditions, which results in their still large size (despite the low-volume formed by the absorption cells) in comparison to field-deployable bulk-optics based sensors [63] and most commonly used in real-life applications non-optical gas detectors [64,65]. However, further minimization of the electronic components, accompanied with optics-free light coupling into the fiber and the possibility of bending the fiber with bend radius in the range of a few centimeters [29,66] should result in a significant reduction in the size of ARHCF-aided gas sensors, even beating the dimensions of the sensors utilizing multipass cells delivering several tens of meters long optical path lengths.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in the transmission properties of the ARHCFs should also allow them to be successfully used in the broadband spectroscopy applications, i.e., in the frequency comb spectroscopy [62], which will enable an in-depth analysis of the complex mixture of gaseous substances, maintaining a low-volume of the sensing unit with high detection capability. Currently, the ARHCF-based gas sensors are in majority realized in laboratory conditions, which results in their still large size (despite the low-volume formed by the absorption cells) in comparison to field-deployable bulk-optics based sensors [63] and most commonly used in real-life applications non-optical gas detectors [64,65]. However, further minimization of the electronic components, accompanied with optics-free light coupling into the fiber and the possibility of bending the fiber with bend radius in the range of a few centimeters [29,66] should result in a significant reduction in the size of ARHCF-aided gas sensors, even beating the dimensions of the sensors utilizing multipass cells delivering several tens of meters long optical path lengths.…”
Section: Discussionmentioning
confidence: 99%
“…A very interesting route for designing novel materials is combining theory and experiment [ 129 , 130 ]. It has been demonstrated that combining experimental results and DFT calculations is very efficient for designing novel toxic-gas sensors [ 131 , 132 , 133 ]. Therefore, in this section, we analyze the coupled theoretical and experimental studies on developed on CNTs modified through surface functionalization and defect engineering to improve the sensitivity and selectivity to NO x .…”
Section: Combined Theoretical and Experimental Studiesmentioning
confidence: 99%
“…Gas sensors are defined by important features, such as the selectivity and sensitivity [12][13][14]. Since selectivity is mostly related to the chemical structure of the gas-sensing materials and its capability to selectively detect target gas molecules, sensitivity relies on the physical structure described as the surface-volume ratio [15]. Therefore, the possibility to deposit a gas-sensing layer of a nanocolumnar shape under controlled conditions is a powerful tool.…”
Section: Introductionmentioning
confidence: 99%